2013
DOI: 10.1177/1753465813503029
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial role of vitamin D3 in the prevention of certain respiratory diseases

Abstract: There is evidence of aberrations in the vitamin D-endocrine system in subjects with respiratory diseases. Vitamin D deficiency is highly prevalent in patients with respiratory diseases, and patients who receive vitamin D have significantly larger improvements in inspiratory muscle strength and maximal oxygen uptake. Studies have provided an opportunity to determine which proteins link vitamin D to respiratory pathology, including the major histocompatibility complex class II molecules, vitamin D receptor, vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 252 publications
(263 reference statements)
0
4
0
Order By: Relevance
“…VDR gene is located on q12-23 loci on chromosome 12, which can be combined with VDR receptor in the target cells, so as to adjust the structure of the corresponding gene ( 17 ). It has been reported that ( 18 , 19 ) the expression of VDR is associated with pulmonary micro-environment development, that is, when there is a lack of VDR, while it is simulated by inflammatory factor, the simulation of lung inflammation is relatively light, revealing that the lack of VDR plays a protective role on asthma. In this study, the level of vitamin D was lower in the observation group than that in the control group (P<0.05); the level of total serum IgE was higher in the observation group than that in the control group (P<0.05), indicating that vitamin D can mediate body's immunity, which is conducive to assessing the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…VDR gene is located on q12-23 loci on chromosome 12, which can be combined with VDR receptor in the target cells, so as to adjust the structure of the corresponding gene ( 17 ). It has been reported that ( 18 , 19 ) the expression of VDR is associated with pulmonary micro-environment development, that is, when there is a lack of VDR, while it is simulated by inflammatory factor, the simulation of lung inflammation is relatively light, revealing that the lack of VDR plays a protective role on asthma. In this study, the level of vitamin D was lower in the observation group than that in the control group (P<0.05); the level of total serum IgE was higher in the observation group than that in the control group (P<0.05), indicating that vitamin D can mediate body's immunity, which is conducive to assessing the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show that vitamin D plays a role in regulating immune cells and modulating the immune response. In several studies, the anti‐inflammatory and immunomodulatory effect of vitamin D on inflammatory diseases, particularly on respiratory viruses such as influenza, respiratory syncytial virus (RSV), Middle East Respiratory Syndrome Coronavirus (MERS‐CoV), SARS‐CoV‐1 and rhinovirus, is shown (Greiller & Martineau, 2015 ; Lương & Nguyễn, 2013 ; Sutaria et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nucleotide methylation can also offer antibiotic resistance, such as 16S rRNA methyltransferase in Enterobacteriaceae 38 . It has been previously been reported that the upregulation of thiamine phosphate synthase can cause an increase in resistance to multiple stresses in Schizosaccharomyces , and thiamine supplementation might also contribute to chemotherapy resistance in cancer cells 39, 40 . Another key upregulated gene glmM (2.6-fold change), encoding phosphoglucosamine mutase, has been demonstrated to contribute to the resistance of Streptococcus , and is the drug target for regulating resistance.…”
Section: Discussionmentioning
confidence: 99%